Pelatihan Pengolahan Porang Untuk Meningkatkan Economic Value Added Dan Market Value Added Petani Porang di Desa Bontolempangan - Mattunruang, Andi Aris; Asmirawati, Asmirawati; Aris, Khaeruddin (Journal Of Human And Education (JAHE), 2024)
Porang Processing Training to Increase Economic Value Added (EVA) and Market Value Added (MVA) of Porang Farmers in Bontolempangan Village aims to increase the economic and market added value of porang products produced by local farmers. This training emphasizes efficient porang processing techniques, optimal business management, and effective marketing strategies. The training materials include porang processing techniques from fresh tubers into processed products such as porang flour and chips, as well as product quality standards to meet market demand. In addition, the training also covers aspects of business management such as business planning, financial management, and production efficiency. Marketing and sales strategies are also highlighted to increase access to the market and build a strong distribution network. With this training, it is hoped that porang farmers in Bontolempangan Village can utilize better processing techniques to increase product added value (EVA) and obtain better selling prices and wider market reach (MVA). Evaluation and follow-up will be carried out to ensure practical implementation of the knowledge gained, as well as support the success of farmers' businesses in the long term. This training is expected to have a positive impact on the welfare of farmers and the village economy as a whole.